EVALUASI SISTEM INFORMASI MANAJEMEN KLINIK NARENDRA MEDIKA - Florentina Nadira Saniman; Bajeng Nurul Widyaningrum; Destri Maya Rani (MEDIKA TRADA, 2024)
Clinic Management Information System (Clinic MIS) is a technology-based system that manages administrative data, medical records, and health services in clinics, which aims to improve operational efficiency and service quality through integrated information management. Considering the importance of the Minister of Health Regulation Number 24 of 2022 for the electronic medical record (EMR) system, this research using the Technology Acceptance Model (TAM) method aims to evaluate the extent to which the Narendra Medika Clinic SIM is accepted by users and to find potential obstacles in daily implementation. This study measures four dimensions of TAM: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention to Use. This research method was descriptive qualitative research, where data was obtained through interviews with health workers at Narendra Medika Clinic who have used the Clinic MIS for more than 6 months. The study results indicate that Clinic MIS has provided significant benefits, especially in supporting health services in the digitalization era. However, there are several obstacles, especially related to the stability of the internet network that need to be improved to ensure smooth operations. Although the accuracy of the information in Clinic MIS is good, several improvements to the features and appearance of the system, such as grouping drug stocks and updating ICD codes, are needed to improve the accuracy and convenience of use by health workers. This study recommends improving network infrastructure and developing additional features in Clinic MIS to support more optimal clinic performance.